2019
DOI: 10.1016/j.jfda.2018.05.001
|View full text |Cite
|
Sign up to set email alerts
|

A steroidal derivative from Trigonella foenum graecum L. that induces apoptosis in vitro and in vivo

Abstract: Trigonella foenum graecum L. is a dietary herb used in traditional medicine system. In this study, we investigated the cytotoxicity, antitumor, antimetastatic and antiangiogenic effect of the steroidal compound, ethyl iso-allocholate isolated from T. foenum graecum L. seeds against A549 lung cancer cells in vitro and in vivo . Among all the isolated compounds, the ethyl iso-allocholate rendered the highest cytotoxicity potential. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(16 citation statements)
references
References 26 publications
0
16
0
Order By: Relevance
“…Compounds 2 and 3 appeared as yellowish oil and were isolated from the hexane fraction of C. timorensis leaf extract. Compound 2, characterized as benzenepropanoic acid, was recently isolated from Trigonella foenum (Fabaceae) and demonstrated to have anti-cancer potential through in vitro and in vivo studies [ 26 ]. To the best of our knowledge, there was no report on the isolation of this compound from the genus Cassia , although it has been reported to be present in C. fistula seeds as identified from GC-MS [ 27 ].…”
Section: Resultsmentioning
confidence: 99%
“…Compounds 2 and 3 appeared as yellowish oil and were isolated from the hexane fraction of C. timorensis leaf extract. Compound 2, characterized as benzenepropanoic acid, was recently isolated from Trigonella foenum (Fabaceae) and demonstrated to have anti-cancer potential through in vitro and in vivo studies [ 26 ]. To the best of our knowledge, there was no report on the isolation of this compound from the genus Cassia , although it has been reported to be present in C. fistula seeds as identified from GC-MS [ 27 ].…”
Section: Resultsmentioning
confidence: 99%
“…Ethyl iso-allocholate interacted strongly with all the protein targets especially caspase-1. This compound is a steroidal derivative with several therapeutic activities including anti-inflammatory and anti-tumour activities [41,42]. Its anti-inflammatory activity could be linked with its interaction and possible modulation of these protein targets.…”
Section: •àmentioning
confidence: 99%
“…Ethyl isoallocholate, otherwise called ethyl cholate, was observed in the HMEL of C. lancifolius, reported for the antibacterial property (Malathi et al, 2016). However, a recent study has demonstrated reduced tumor growth (Thakur and Ahirwar, 2019). Caryophyllene oxide is a bicyclic sesquiterpene observed in the HMEL of C. lancifolius and has been shown as an anticancer molecule (Pan et al, 2016).…”
Section: Discussionmentioning
confidence: 99%